2012
DOI: 10.1108/02683941211193875
|View full text |Cite
|
Sign up to set email alerts
|

Moral leadership and psychological empowerment in China

Abstract: PurposeThe purpose of this study is to examine the mediating role of perceived procedural justice and interactional justice on the relationship between moral leadership and the four psychological empowerment dimensions manifested in individuals' perceptions of meaning, competence, self‐determination, and impact.Design/methodology/approachData from 241 subordinates, who reported to 110 supervisors, were collected from clothing companies in southern mainland China. The subordinates responded to a self‐report sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 51 publications
3
36
0
Order By: Relevance
“…Some researchers (e.g., Kirkman et al 2009;Pillai et al 1999) have argued that leaders should have some crucial influences on employees' perceptions of organization-focused justice (i.e., procedural and distributive justice). As ethical leaders act as organization's moral agents who maintain and promote the compliance of ethical standard of the organization such as fairness, one may expect that their behaviors have an important role to play in affecting employees' fairness judgment regarding organizational procedures and outcomes (Demirtas 2013;Li et al 2012. In this study, we examine these relationships by proposing trust in organization as a key mediating mechanism.…”
Section: Ethical Leadership Trust In Organization and Justice Percementioning
confidence: 95%
See 1 more Smart Citation
“…Some researchers (e.g., Kirkman et al 2009;Pillai et al 1999) have argued that leaders should have some crucial influences on employees' perceptions of organization-focused justice (i.e., procedural and distributive justice). As ethical leaders act as organization's moral agents who maintain and promote the compliance of ethical standard of the organization such as fairness, one may expect that their behaviors have an important role to play in affecting employees' fairness judgment regarding organizational procedures and outcomes (Demirtas 2013;Li et al 2012. In this study, we examine these relationships by proposing trust in organization as a key mediating mechanism.…”
Section: Ethical Leadership Trust In Organization and Justice Percementioning
confidence: 95%
“…Their emphasis on the adherence to organizational policies and practices draw employees' attention to the organization's fair procedures (Loi et al 2012). In their study conducted in China, Li et al (2012) found that subordinates under ethical leaders perceive greater procedural justice.…”
Section: Ethical Leadership Trust In Organization and Justice Percementioning
confidence: 98%
“…Research on paternalistic leadership suggests that moral leadership is strongly related to positive employee attitudes and behavior (Farh et al, 2006). Moral leadership has an effect on employees' trust in the leader (Li et al, 2012;Wu et al, 2012). In the moral leadership style, leaders demonstrate high standards of trustworthiness and…”
Section: 9mentioning
confidence: 99%
“…A number of studies have analyzed the relationship between paternalistic leadership styles (authoritarian, benevolent, and moral) and innovative behavior and suggested that paternalistic leadership influences innovative behavior [6][7][8]. When leaders with moral leadership styles give employees autonomy and independence, employees become able to influence what happens in their jobs and feel empowered [9]. Moreover, when benevolent leaders support employees [6] and provide them with task related resources [10], it gives employees a sense of power [11].…”
Section: Introductionmentioning
confidence: 99%